Enteric virome of Ethiopian children participating in a clean water intervention trial. - Eda Altan; Kristen Aiemjoy; Tung G Phan; Xutao Deng; Solomon Aragie; Zerihun Tadesse; Kelly E Callahan; Jeremy Keenan; Eric Delwart (PLoS ONE, 2018)
BACKGROUND:The enteric viruses shed by different populations can be influenced by multiple factors including access to clean drinking water. We describe here the eukaryotic viral genomes in the feces of Ethiopian children participating in a clean water intervention trial. METHODOLOGY/PRINCIPAL FINDINGS:Fecal samples from 269 children with a mean age of 2.7 years were collected from 14 villages in the Amhara region of Ethiopia, half of which received a new hand-dug water well. Feces from these villages were then analyzed in 29 sample pools using viral metagenomics. A total of 127 different viruses belonging to 3 RNA and 3 DNA viral families were detected. Picornaviridae family sequence reads were the most commonly found, originating from 14 enterovirus and 6 parechovirus genotypes plus multiple members of four other picornavirus genera (cosaviruses, saliviruses, kobuviruses, and hepatoviruses). Picornaviruses with nearly identical capsid VP1 were detected in different pools reflecting recent spread of these viral strains. Next in read frequencies and positive pools were sequences from the Caliciviridae family including noroviruses GI and GII and sapoviruses. DNA viruses from multiple genera of the Parvoviridae family were detected (bocaviruses 1-4, bufavirus 3, and dependoparvoviruses), together with four species of adenoviruses and common anelloviruses shedding. RNA in the order Picornavirales and CRESS-DNA viral genomes, possibly originating from intestinal parasites or dietary sources, were also characterized. No significant difference was observed between the number of mammalian viruses shed from children from villages with and without a new water well. CONCLUSIONS:We describe an approach to estimate the efficacy of potentially virus transmission-reducing interventions and the first complete (DNA and RNA viruses) description of the enteric viromes of East African children. A wide diversity of human enteric viruses was found in both intervention and control groups. Mammalian enteric virome diversity was not reduced in children from villages with a new water well. This population-based sampling also provides a baseline of the enteric viruses present in Northern Ethiopia against which to compare future viromes.